Testing the Fill‐and‐Spill Model of Subsurface Lateral Flow Using Ground‐Penetrating Radar and Dye Tracing - Nyquist, J.E. (2020)
The site was then excavated to the soil–saprock interface and photographed to document the dye pathways. We observed vertical dye fingering near the infiltration trench. Downslope lateral PF at the soil–saprock boundary was limited to ~0.40 m, which is evidence that the soil–saprock interface did not fill‐and‐spill. The extent, depth, and direction of the downslope PF indicated by GPR generally matched the dye staining patterns in the excavation, but the resolution of the 800‐MHz GPR antenna was insufficient to distinguish small fingers of dye. A revised fill‐and‐spill model was proposed for this site that incorporates the PF through fractured saprock before water encounters fresh bedrock surface. This study demonstrates that GPR integrated with dye tracer infiltration can provide a useful means of testing hillslope hydrological hypotheses and unraveling the complexity of PF at the hillslope scale in a field setting.